Affirmative Action for Muslims? Arguments, Contentions and Alternatives. (December 2014) - Alam, Mohd. Sanjeer
India is one of the most unequal societies of the world. At the same time, it has the distinction of having the longest history of affirmative action programmes for alleviating socio-economic inequalities. Currently, three social groups—the Scheduled Castes (SCs), the Scheduled Tribes (STs) and the Other Backward Classes (OBCs)—enjoy the benefits of affirmative action programmes, of reservation in particular. However, the demands to get acknowledged as 'disadvantaged' and for inclusion in the system of affirmative action have not stopped. Of late, the demands for reservation for disadvantaged minorities, Muslims in particular, have ignited intense and polarized debates. All this has not only complicated the politics of 'recognition' and 'redistribution' but also affected the discourse on and capacity of existing affirmative measures to tackle the issue of group-based disadvantages. Against this backdrop, the objective of this article is two-fold: ( a ) to get into the complexities underlying the idea of affirmative action for Muslims; and ( b ) to move the debates on affirmative action beyond 'one policy fits all' perspective.